2011
DOI: 10.1088/0029-5515/51/8/083034
|View full text |Cite
|
Sign up to set email alerts
|

Stable plasma start-up in the KSTAR device under various discharge conditions

Abstract: A time series of static nonlinear ferromagnetic calculations was performed to mimic the time-dependent modelling of plasma start-up by assessing the effects of the ferromagnetic Incoloy 908 used in the superconducting coil jackets of the Korea Superconducting Tokamak Advanced Research (KSTAR) device. Time-series calculations of a two-dimensional axisymmetric circuit model with nonlinear ferromagnetic effects enabled us to find appropriate waveforms for the KSTAR poloidal field coil currents that satisfied vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…We also developed a multi-dimensional particle simulation code BREAK to verify the theoretical model and to systematically investigate dynamic plasma evolutions in the realistic complex electromagnetic structures. BREAK is applied to simple artificial scenarios and a reference ohmic breakdown scenario of KSTAR 26 (see Methods).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…We also developed a multi-dimensional particle simulation code BREAK to verify the theoretical model and to systematically investigate dynamic plasma evolutions in the realistic complex electromagnetic structures. BREAK is applied to simple artificial scenarios and a reference ohmic breakdown scenario of KSTAR 26 (see Methods).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…During the first year of KSTAR operation, there was a significant fraction of the discharges that would move onto the inner wall and terminate early and it was not possible to produce a discharge without the use of ECRH assist. An analysis of the field pattern around the time of breakdown by J. Kim 34 , which included the effects of the ferromagnetic material, indicated that the vertical field near the central column was larger than was indicated by calculations that did not take the ferromagnetic material effect into account. There was a region inside some major radius where n>3/2 and the plasma was radially unstable.…”
Section: E Examples From East and Kstarmentioning
confidence: 92%
“…From the result of a nonmagnetic analysis [4], it was found that the ferromagnetic effect of Incoloy 908 distorts the actual magnetic field to which the plasma current responds. The distortion of the magnetic field is particularly critical during the start-up stage because the plasma current channel is very sensitive to external magnetic fields due to the low plasma current level.…”
Section: Incoloy Effect On Startupmentioning
confidence: 99%